Stroke‐prevention strategies in North American patients with atrial fibrillation: The GLORIA‐AF registry program. Issue 6 (10th May 2018) - McIntyre, William F.; Conen, David; Olshansky, Brian; Halperin, Jonathan L.; Hayek, Emil; Huisman, Menno V.; Lip, Gregory Y.H.; Lu, Shihai; Healey, Jeff S.
Abstract : Background: Antithrombotic prophylaxis with oral anticoagulation (OAC) substantially reduces stroke and mortality in patients with atrial fibrillation (AF). Hypothesis: Analysis of data in the Global Registry on Long‐Term Antithrombotic Treatments in Patients With Atrial Fibrillation (GLORIA‐AF), an international, observational registry of patients with newly diagnosed AF, can identify factors associated with treatment decisions and outcomes. Methods: Multivariable regression identified patient, physician, and temporal factors associated with OAC prescription, compared with management with antiplatelet drugs or no antithrombotic drugs in North American patients enrolled between November 2011 and February 2014. Results: Of 3320 eligible patients (mean age, 71 ± 11 years; 1879 males with CHA2 DS2 ‐VASc ≥1 and 1441 females with CHA2 DS2 ‐VASc ≥2), 79.3%, 12.5%, and 7.4% received OAC, antiplatelet drugs, or no antithrombotic therapy, respectively. Of those prescribed OAC, 66.4% received non–vitamin K antagonist oral anticoagulation and 24.5% received concomitant therapy with antiplatelet drugs. Independent predictors of OAC therapy were nonparoxysmal AF (odds ratio, 95% confidence interval: 2.02, 1.56–2.63), prior stroke/transient ischemic attack (2.00, 1.37–2.92), specialist care (1.50, 1.04–2.17), more concomitant medications (1.47, 1.13–1.92), commercial insurance (1.41, 1.07–1.85), and heart failure (1.44, 1.07–1.92). Antiplatelet drugs (0.18, 0.14–0.23), prior falls (0.41, 0.27–0.63), and prior bleeding (0.50, 0.35–0.72) were inversely associated with OAC prescription. Conclusions: In GLORIA‐AF, 20% of the population comprising males with CHA2 DS2 ‐VASc ≥1 and females with CHA2 DS2 ‐VASc ≥2 did not receive OAC therapy. Patient characteristics associated with a lower likelihood of OAC prescription were use of antiplatelet drugs, paroxysmal pattern of AF, history of falls, and prior bleeding.